2021
DOI: 10.3390/ijerph18115928
|View full text |Cite
|
Sign up to set email alerts
|

Rodent-Related Zoonotic Pathogens at the Human–Animal–Environment Interface in Qatar: A Systematic Review and Meta-Analysis

Abstract: Rodents are one of the most diversified terrestrial mammals, and they perform several beneficial activities in nature. These animals are also important as carriers of many pathogens with public health importance. The current systematic review was conducted to formulate a true depiction of rodent-related zoonoses in Qatar. Following systematic searches on PubMed, Scopus, Science Direct, and Web of Science and a screening process, a total of 94 published articles were selected and studied. The studied articles r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 150 publications
0
5
0
Order By: Relevance
“…DLNM was used to explore the monthly lag effects of different climate factors on HFRS, and the lag effects vary across climatic factors was uncovered. The different lag periods suggested that the delayed effects of each climate variable may be related to the spread of HFRS infection being influenced by various factors, including the density of host rodents, hantavirus positivity, and frequency of exposure to humans, etc 21,22 . DLNM, by Sun et al in Huludao City, Northeast China, conducted and identified extremely high temperature with a lag of 15-16 weeks, extremely low temperature with a lag of 5-6 weeks, extremely high humidity with a 10-11 weeks lag being strongly associated with HFRS.…”
Section: Discussionmentioning
confidence: 99%
“…DLNM was used to explore the monthly lag effects of different climate factors on HFRS, and the lag effects vary across climatic factors was uncovered. The different lag periods suggested that the delayed effects of each climate variable may be related to the spread of HFRS infection being influenced by various factors, including the density of host rodents, hantavirus positivity, and frequency of exposure to humans, etc 21,22 . DLNM, by Sun et al in Huludao City, Northeast China, conducted and identified extremely high temperature with a lag of 15-16 weeks, extremely low temperature with a lag of 5-6 weeks, extremely high humidity with a 10-11 weeks lag being strongly associated with HFRS.…”
Section: Discussionmentioning
confidence: 99%
“…This variation could be explained by the observed differences in the abundance and diversity of rodents from different sampled habitats, as earlier explained by Mardosaitė et al (2021). Additionally, close contacts between rodent species, humans and other animals in human-related activities may contribute to the variation in prevalence (Islam et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…Hantavirus Pulmonary Syndrome is contracted via direct transmission through breathing in aerosolized secretions from rats [70]. Indirectly, rats could transmit diseases to human through stepping on household water sources, food, clothing and floors [71] and exposure to air-bone diseases from rats through inhaling sweeping dust can also occur [72]. Peridomestic rats are sentinels, reservoir and vectors in the transmission of AMR pathogens to humans and other animals since they share similar environment with people, domestic pets and insect vectors [47].…”
Section: Discussionmentioning
confidence: 99%